Utilization of Jhama brick dust as a sustainable alternative for fine aggregate in concrete - Mohammed Shakeeb Ulla Khan; Pranali Sanjay Patil (International Journal of Science, Technology, Engineering and Mathematics)
The construction industry is constantly seeking sustainable alternatives to traditional materials due to growing environmental concerns and resource depletion. This study explores the potential of using Jhama Brick Dust (JBD) as a substitute for fine aggregate in concrete. Jhama bricks, which are over-burnt bricks, often considered waste, were processed into fine dust and incorporated into concrete mixes at varying percentages (0%, 10%, 20%, 30%, and 40%) to partially replace natural sand. The concrete mixes were tested for their workability, compressive strength, tensile strength, and durability. Results showed that concrete containing 20% JBD as a replacement for fine aggregate exhibited a compressive strength increase of 8% compared to the control mix. The tensile strength also improved by 5% at the same replacement level. However, higher replacements of 30% and 40% showed a decline in both strength and workability. Durability tests revealed that concrete with 20% JBD had better resistance to water penetration, making JBD suitable for applications requiring enhanced durability. This research indicates that Jhama Brick Dust can serve as a sustainable, cost-effective material in concrete production, offering potential cost savings and broader applicability within the industry due to its performance and availability. Incorporating JBD as a partial replacement for fine aggregate contributes to sustainable construction practices while maintaining satisfactory mechanical properties.